Innovative Tool Coatings for Increasing Tool Life in Milling Nickel-coated Nickel-silver Alloy. (2015) - Sortino, Marco; Belfio, Sandro; Totis, Giovanni; Kuljanic, Elso; Fadelli, Giovanni
Abstract: In the automotive market, there is a strong interest for the production of sidewinder keys made of Nickel-coated Nickel-Silver alloy. The Nickel coating improves wear resistance and brightness of the key, nevertheless it reduces the machinability and the tool life when milling the key groove is short. In this work, several innovative tool coatings were applied on conventional mills to enhance the machinability of Nickel-coated Nickel-Silver alloy. Tool life and burr formation obtained with the tested tools were investigated and discussed. Some of the coatings proved to be very promising for this application thank to their excellent tool life. Specifically, the PCD tool was the most interesting since the tool life was significantly longer than conventional carbide tool.